2007
DOI: 10.1007/s11010-007-9614-3
|View full text |Cite
|
Sign up to set email alerts
|

Metformin promotes isolated rat liver mitochondria impairment

Abstract: Metformin, a drug widely used in the treatment of type 2 diabetes, has recently received attention due to the new and contrasting findings regarding its effects on mitochondrial function. In the present study, we evaluated the effect of metformin in isolated rat liver mitochondria status. We observed that metformin concentrations ‡8 mM induce an impairment of the respiratory chain characterized by a decrease in RCR and state 3 respiration. However, only metformin concentrations ‡10 mM affect the oxidative phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 42 publications
3
64
2
Order By: Relevance
“…Interestingly, metformin has been documented to prevent cell death by modulation of the mitochondrial permeability transition pore opening induced by a glutathione-oxidising agent t-butyl hydroperoxide (Guigas et al 2004) and also due to high glucose-induced cell death in a human dermal microvascular endothelial cell line, HMEC-1 (Detaille et al 2005). However, reports of metformin treatment resulting in an increase in H 2 O 2 production in rat liver mitochondria (Carvalho et al 2008), a short-term trial involving 15 type 2 diabetes mellitus patients treated with metformin showing an elevation in oxidative stress, indicated by elevated malidialdehyde levels (Škrha et al 2007) and metformin causing mitochondrial depolarization and oxidative stressdependent apoptosis in cultured glioma cells (Isakovic et al 2007), suggest that the role of mitochondria in metformininduced cytotoxicity remains to be of defined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, metformin has been documented to prevent cell death by modulation of the mitochondrial permeability transition pore opening induced by a glutathione-oxidising agent t-butyl hydroperoxide (Guigas et al 2004) and also due to high glucose-induced cell death in a human dermal microvascular endothelial cell line, HMEC-1 (Detaille et al 2005). However, reports of metformin treatment resulting in an increase in H 2 O 2 production in rat liver mitochondria (Carvalho et al 2008), a short-term trial involving 15 type 2 diabetes mellitus patients treated with metformin showing an elevation in oxidative stress, indicated by elevated malidialdehyde levels (Škrha et al 2007) and metformin causing mitochondrial depolarization and oxidative stressdependent apoptosis in cultured glioma cells (Isakovic et al 2007), suggest that the role of mitochondria in metformininduced cytotoxicity remains to be of defined.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial complex I is also one of the main sites at which reactive oxygen species can be generated (Brownlee 2001;Nishikawa et al 2000). Metformin has also been reported to increase H 2 O 2 production in rat liver mitochondria and exacerbated Ca 2+ -induced mitochondrial permeability pore opening in a concentration-dependent manner (Carvalho et al 2008). Moreover, metformin in cultured glioma cells has been shown to cause mitochondrial depolarization and oxidative stress-dependent apoptosis (Isakovic et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mice remained tumor free for at least 2 months after the combined treatment was ended. Moreover, a recent study 56 has documented that the positive charge of metformin could promote its accumulation within the mitochondrial matrix by 1000-fold (420 mM). It has also been demonstrated that metformin accumulates in tissues at concentrations several fold higher than those in blood, 57 indicating that AMPK-related active concentrations of metformin employed in preclinical settings might be attained also during cancer treatment in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on cells, animals and mitochondria isolated from human skeletal muscle samples have shown conflicting results [9][10][11][12][13]. Studies carried out on rat muscle (permeabilised fibres and isolated mitochondria) or liver or in cell lines may not be representative of skeletal muscle from human patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin possibly enhances peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) levels and mitochondrial biogenesis via AMPK phosphorylation in skeletal muscles [8]. Metformin treatment has also been associated with inhibition of complex I in the mitochondrial electron transport chain in studies of rat muscle or liver and in studies using cell lines [9][10][11][12]. A recent study on rat skeletal muscle suggested that a possible inhibitory effect of metformin on mitochondrial respiration was concentration-dependent [13] with no effect of metformin in concentrations up to 1.0 mmol/l in the vicinity of the mitochondria.…”
Section: Introductionmentioning
confidence: 99%